Influence of the Coordinated Transition Metal Ion on Magnetic Relaxation of Lanthanide Based Complexes with Imino Nitroxide Biradical Ligands. Issue 65 (19th September 2022) - Xi, Lu; Jin, Chaoyi; Song, Hongwei; Wang, Xiaotong; Xie, Junfang; Ma, Yue; Tang, Jinkui; Li, Licun
Abstract: In spite of achievement of a lot of Ln‐radical SMMs, how to improve magnetic behavior of Ln‐radical system remains challenging. Here, two series of Ln‐radical complexes have successfully been built using an imino nitroxide biradical, namely, [Ln2 (hfac)6 (ImPhPyobis)2 ] (Ln III =Gd 1, Tb 2, Dy 3 ) and [Ln2 Cu2 (hfac)10 (ImPhPyobis)2 ] (Ln III =Gd 4, Dy 5 ; hfac=hexafluoroacetylacetonate and ImPhPyobis=5‐(4‐oxypyridinium‐1‐yl)‐1, 3‐bis(1'‐oxyl‐4', 4', 5', 5'‐tetramethyl‐4, 5‐hydro‐1 H ‐imidazol‐2‐yl)benzene). For these biradical‐metal complexes, two imino nitroxide biradicals bind two Ln(III) ions via their oxygen atoms coming from 4‐oxypyridinium units to produce a binuclear Ln2 O2 unit. Those imino nitroxide groups are free for complexes 1 –3, however one of imino nitroxide groups of the biradical is ligated to the copper(II) ion for complexes 4 and 5 . The distinct magnetic relaxation behaviors are observed for two Dy derivatives, as revealed by ac magnetic studies: complex 3 presents one magnetic process with the effective energy barrier( U eff ) of 74.0 K while complex 5 exhibits dual relaxation processes with U eff values for the fast‐ and slow‐relaxation being 20.2 K and 30.9 K, respectively, which implies that the second coordination sphere of Dy ion plays a critical role for magnetic relaxation. Abstract : Two series of biradical‐metal complexes have been obtained by using an imino nitroxide biradical. Remarkably one magnetic process is found for the Dy‐biradical compound while the Dy−Cu‐radical compound exhibits dual relaxation processes which indicates that the second coordination sphere of Dy ion plays a crucial role in magnetic relaxation behavior.